Honor and Grace in Anthropology - Peristiany, John George 1911-198; Pitt-Rivers, Julian Alfred (Cambridge, New York, Port Chester : Cambridge University Press, 1992)
LAFAGES (C.), Royalty and Ritual in the Middle Ages : Coronation and funerary rites in France
LEROY LADURIE (E.), The Court Surrounds the King : Louis XIV, the Palatine Princess and Saint-Simon
BOURDIEU (P.), Rites as Acts of Institution
CARO BAROJA (J.), Religion, World Views, Social Classes and Honor during the Sixteenth and Seventeenth Centuries in Spain
PERISTIANY (J.G.), The Sophron - a Secular Saint ? Wisdom and the Wise in a Cypriot Community
CAMPBELL (J.K.), The Greek Hero
DI BELLA (M.P.), Name, Blood and Miracles : The claims to renown in traditional Sicily
JAMOUS (R.), From the Death of Men to the Peace of God : Violence and peace-making in the Rif
OTT (S.), Indarra : Some reflections on a Basque Concept
PITT-RIVERS (J.), Postscript : The place of grace in anthropology
Current Anthropology, 34(3), 1993, pp. 330-334 (Charles Stewart)
bibliogr. dissém.